2006
DOI: 10.1051/0004-6361:20064956
|View full text |Cite
|
Sign up to set email alerts
|

4U 1344-60: a bright intermediate Seyfert galaxy atz= 0.012 with a relativistic Fe K$\mathsf{\alpha}$ emission line

Abstract: We present analysis of the optical and X-ray spectra of the low Galactic latitude bright (F 2−10 = 3.6 × 10 −11 erg cm −2 s −1 ) source 4U 1344−60. On the basis of the optical data we propose to classify 4U 1344−60 as an intermediate type Seyfert galaxy and we measure a value of z = 0.012 ± 0.001 for its redshift. From the XMM-Newton observation we find that the overall X-ray spectral shape of 4U 1344−60 is complex and can be described by a power-law continuum (Γ ≈ 1.55) obscured by two neutral absorption comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 60 publications
(78 reference statements)
6
30
0
Order By: Relevance
“…Although its X-ray spectrum is heavily absorbed by the Galactic interstellar matter (N H ≈ 1 × 10 22 cm −2 ) it has clearly revealed an emission excess in the broadened red wing of the iron line in a previous XMM-Newton observation (Piconcelli et al 2006). 4U 1344-60 was discovered for the first time by the X-ray satellite Uhuru.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Although its X-ray spectrum is heavily absorbed by the Galactic interstellar matter (N H ≈ 1 × 10 22 cm −2 ) it has clearly revealed an emission excess in the broadened red wing of the iron line in a previous XMM-Newton observation (Piconcelli et al 2006). 4U 1344-60 was discovered for the first time by the X-ray satellite Uhuru.…”
Section: Introductionmentioning
confidence: 70%
“…4U 1344-60 also exhibited a complex absorption in the X-ray spectrum. Piconcelli et al (2006) suggested the presence of a partially covering absorber to explain a remarkably flat power law describing the data. A combined analysis of the XMM-Newton and INTEGRAL observation was later done by Panessa et al (2008) who concluded that the spectrum is affected by one fully and two partially covering absorbers with substantial column densities (N pc1 H ≈ 5 × 10 22 cm −2 , and N pc2 H ≈ 4 × 10 23 cm −2 ) and covering fractions around 50%.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations